Answer:
uhm
Step-by-step explanation:
An algebraic expression doesnt have an equals sign or an inequality sign.
So,
A is an expression
B is an inequality
C is an equation
D is an in inequality
So the answer is A
Answer:
![x=-9](https://tex.z-dn.net/?f=x%3D-9)
Step-by-step explanation:
We translate the phrase into an equation:
![2+3(x-5)=4(x-1)\\](https://tex.z-dn.net/?f=2%2B3%28x-5%29%3D4%28x-1%29%5C%5C)
Then we simplify:
![2+3(x-5)=4(x-1)\\2+3x-15=4x-4\\-13+3x=4x-4\\-9=x](https://tex.z-dn.net/?f=2%2B3%28x-5%29%3D4%28x-1%29%5C%5C2%2B3x-15%3D4x-4%5C%5C-13%2B3x%3D4x-4%5C%5C-9%3Dx)